Persistent burden and health inequalities of lung cancer among adolescents and young adults, 1990-2021 - Li, Jianhui; Wang, Ju-zi; Chen, Qihui; Qin, Miaomiao; Zhang, Jing; Liu, Hui; Xun, Yingpin (Frontiers in Oncology, 2025)
BackgroundTo assess the disease burden, trends, health inequality, and risk factors of lung cancer among adolescents and young adults (AYAs) during the period from 1990 to 2021.MethodsA secondary analysis was conducted using the Global Burden of Disease (GBD) 2021, focusing on the temporal trends, decomposition analysis, health inequality and risk factors of lung cancer burden among AYAs.ResultsGlobally, the rate of lung cancer among AYAs decreased between 1990 and 2021, with the age-standardized incidence rate (ASIR) decreasing from 1.3 (95% uncertainty interval [UI], 1.2 to 1.4) to 0.9 (95% UI, 0.8 to 1.0, AAPC = -1.2), age-standardized mortality rate (ASMR) decreasing from 1.1 (95% UI, 1.0 to 1.2) to 0.7 (95% UI, 0.6 to 0.8, AAPC = -1.4), and age-standardized disability-adjusted life years rate (ASDR) decreasing from 65.4 (95% UI, 60.2 to 71.1) to 42.1 (95% UI, 37.7 to 46.5, AAPC = -1.4). The global number of lung cancer among AYAs has only undergone slight changes, but the middle socio-demographic index (SDI) region, East Asia and China carried heavier lung cancer burden. Notably, the only increase in ASIR, ASDR, and ASMR was found in the low-middle SDI and low SDI regions, especially among women. Decomposition analysis showed that population growth and population aging are the primary driving forces behind the increasing lung cancer burden among AYAs. Smoking was the leading specific risk factor for men and the overall population in 2021, while ambient particulate matter pollution was identified as the leading specific risk for women. Health inequality analysis indicated that the absolute health inequalities marginally declined, while relative health inequalities remained relatively high, and the lung cancer burden among AYAs was predominantly in wealthier countries.ConclusionsWhile global ASIR, ASDR, and ASMR of lung cancer among AYAs have declined from 1990 to 2021, cross-national health inequality remained elevated and sustained, particularly in wealthier countries. Increased attention needs to be given to the lung cancer burden among AYAs in low- and middle-income countries and among women, while risk factors such as smoking and ambient particulate matter pollution remain critical targets for intervention.